Characteristics and performance of a mesoporous cerium-aluminum-silver mixed oxide for removal of methyl violet dye - Phatai P.; Srisomang R. (Penerbit Universiti Kebangsaan Malaysia, 2016)
oxides was investigated. The properties of mixed oxide were determined by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), N2 adsorption-desorption isotherm, diffuse reflectance UV-vis spectroscopy (UV-vis DRS) and X-ray absorption near edge structure (XANES). Characterization showed that synthesized mixed oxide with fluorite has a pure cubic structure of a mesoporous nature and a small grain size with rough surface. Batch adsorption experiments were used to study parameters including contact time and initial dye concentration. The results showed that these parameters affected the degree of MV dye adsorption. The dye adsorption of mixed oxides attained equilibrium at 120 min. The equilibrium adsorption data were analyzed using Langmuir, Freundlich and Temkin isotherms. The adsorption behavior of MV dye onto Ce0.3Al0.7 was found to follow the Langmuir isotherm (R2 = 0.9951), providing a maximum monolayer adsorptive capacity of 2.35 mg/g. Alternatively, the adsorption of MV dye onto Ce0.3Al0.7Ag0.1 (R2 = 0.7839), Ce0.3Al0.7Ag0.3 (R2 = 0.9301) and Ce0.3Al0.7Ag0.5 (R2 = 0.9396) followed the Freundlich isotherm. The possible adsorption mechanisms of MV dyes onto the Ce0.3Al0.7 and Ce0.3Al0.7Agx were also discussed.